The Power of Religious Organizations in Human Decision Processes: Analyzing Voting Behavior - Benno Torgler; David Stadelmann; Marco Portmann (Center for Research in Economics, Management and the Arts (CREMA), 2013)
In Switzerland, two key church institutions - the Conference of Swiss Bishops (CSB) and the Federation of Protestant Churches (FPC) - make public recommendations on how to vote for certain referenda. We leverage this unique situation to directly measure religious organizations' power to shape human decision making. We employ an objective measure of voters' commitment to their religious organization to determine whether they are more likely to vote in line with this organization's recommendations. We find that voting recommendations do indeed matter, implying that even in a secularized world, religion plays a crucial role in voting decisions.
Keywords: D03; D72; D83; H70; 330; Power; religion; voting; referenda; trust; rules of thumb